The reality of treatment for hyperuricemia and gout in Japan: A historical cohort study using health insurance claims data. Issue 8 (12th July 2022) - Akari, Seigo; Nakamura, Takashi; Furusawa, Kenichi; Miyazaki, Yuichi; Kario, Kazuomi
Abstract: Hyperuricemia causes gout and has also been associated with metabolic syndrome and cardiovascular disease. Uric acid‐lowering drugs (ULDs) are used to reduce uric acid levels for the treatment of hyperuricemia and gout. However, there is a lack of robust and real‐world data on the history and treatment of patients with newly diagnosed hyperuricemia or gout in Japan. This retrospective, longitudinal, historical cohort study determined the characteristics of patients with hyperuricemia and/or gout, and prescription of, and adherence to, ULDs using data from the JMDC Claims Database. The primary evaluation population included 64 677 patients with newly diagnosed hyperuricemia and/or gout. Of these, only 26 501 (41.0%) had a prescription for ULDs at diagnosis. Even when ULDs were prescribed, the persistence rate of prescriptions declined over time, with a 54.4% persistence rate for ULDs at 12 months after the index diagnosis. In subgroups of patients with or without hypertension and diabetes, the rate of ULD prescription continuation was significantly higher in those with comorbidities than in those without (76.8% vs. 42.6% in those with vs. without hypertension, and 78.7% vs. 52.2% in those with vs. without diabetes). These finding suggest that therapeutic interventions to lower serum uric acid levels are under‐utilized for patients with newly diagnosed hyperuricemia and/or gout in Japan.